2012
DOI: 10.1371/journal.pone.0049128
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Glucose 6-Phosphate Dehydrogenase Activity Restores Redox Balance in Vascular Endothelial Cells Exposed to High Glucose

Abstract: Previous studies have shown that high glucose increases reactive oxygen species (ROS) in endothelial cells that contributes to vascular dysfunction and atherosclerosis. Accumulation of ROS is due to dysregulated redox balance between ROS-producing systems and antioxidant systems. Previous research from our laboratory has shown that high glucose decreases the principal cellular reductant, NADPH by impairing the activity of glucose 6-phosphate dehydrogenase (G6PD). We and others also have shown that the high glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 49 publications
3
34
0
Order By: Relevance
“…The synthesis of gluconic acid in bacteria is conducted by membrane-bound glucose dehydrogenase (GDH) 28 . As reported by Zheng et al 36 the magnetic fi eld of a specifi c frequency can increase the activity of this enzyme. Therefore, it can be assumed that the differences in the concentration of gluconic acid observed in the present study could be a result of variances in GDH activity caused by the particular mode of RMF exposure.…”
Section: Analysis Of Cellulose Producing Bacteria and Cellulose Non-psupporting
confidence: 55%
“…The synthesis of gluconic acid in bacteria is conducted by membrane-bound glucose dehydrogenase (GDH) 28 . As reported by Zheng et al 36 the magnetic fi eld of a specifi c frequency can increase the activity of this enzyme. Therefore, it can be assumed that the differences in the concentration of gluconic acid observed in the present study could be a result of variances in GDH activity caused by the particular mode of RMF exposure.…”
Section: Analysis Of Cellulose Producing Bacteria and Cellulose Non-psupporting
confidence: 55%
“…Consistent with this report, we have observed that G6PD knockdown markedly decreased the expression level of NOX subunits in parallel with an absence of NOX induction by TNF-α. G6PD can control nuclear NADPHdependent superoxide production by NOX4 [43], and G6PD is colocalized with NOX in high G6PD Status Affects TNF-α-Triggered COX-2 Response glucose conditions, while providing NADPH for NOX activation [44] is an additional evidence to support the hypothesis that G6PD can modulate NOX activity. Physiologically, the activation of NOX can trigger the production of chemokines and inflammation-associated proteins upon viral infection [19,45,46].…”
Section: Discussionmentioning
confidence: 75%
“…However, G6PD deficiency will cripple the antioxidant defense, resulting in the build‐up of ROS and subsequent oxidative damage. Previously, we and others showed that G6PD deficiency led to increased accumulation of ROS in many cell types, which impaired their cellular function and survival (18, 21). In this study, we report for the first time that high glucose–induced G6PD deficiency in podocytes resulted in increased ROS accumulation and apoptosis, which could be rescued by overexpressing G6PD.…”
Section: Discussionmentioning
confidence: 99%